PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR KOGNITIF FISIKA SISWA DI SMA N 1 TAMBUSAI PADA POKOK BAHASAN USAHA DAN ENERGI - Pasaribu, Rina Yanit; Daruwati, Ika; Febriani, Yeza (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2015)
The research purposed to determine the effect of cooperative learning model Think Pair Share (TPS) to thecognitive learning physics class XI student of Mathematics SMA N 1 Tambusai on the subject of work andenergy. The experiment was conducted at the experimental class with the implementation of cooperativelearning model TPS and control classes with the application of conventional models. The data analysistechnique is the t-test, obtained the price thitung= 3.301 and ttabel = 1.670 for t (3.301> 1.670), then accepted Ha.The findings show there is influence of cooperative learning model TPS to the cognitive learning physics classXI MIPA I SMA N 1 Tambusai.